2015
DOI: 10.1007/s10973-015-4924-2
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Cr–Pb nanocomposites

Abstract: In this study, we present the synthesis of CuCr-Pb nanocomposites by a simple co-precipitation method and evaluate the catalytic performance of the asfabricated Cu-Cr-Pb nanocomposites on the thermal decomposition of ammonium perchlorate (AP). The X-ray diffraction, scanning electron microscopy, transmission electron microscopy and thermogravimetric analysis/differential scanning calorimetric techniques were employed to characterize the crystal phases, sizes and catalytic properties of as-obtained Cu-Cr-Pb nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The lead salt, as the active catalyst in the solid propulsion system, has a positive impact on the combustion rate and performance of the propellant. 13,14 Huo et al introduced a poly(lead acrylate) (PAA-Pb) porous metal material into the AP catalytic system, and the high-temperature decomposition peak of AP was reduced by 73.7 K. 15 The pyrolysis peak of AP was advanced by 95 K when the amount of the complex added was 10 wt %. 12 Cheng et al reported Pb-ANP y O/CNTs nanocomposites, which can reduce the pyrolysis peak of AP by nearly 100 K. 9 However, metallic elements have great limitations because of their high surface energy and tend to lead to agglomeration so that their catalytic activity is low, which has a great impact on the catalytic effect of AP thermal decomposition.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead salt, as the active catalyst in the solid propulsion system, has a positive impact on the combustion rate and performance of the propellant. 13,14 Huo et al introduced a poly(lead acrylate) (PAA-Pb) porous metal material into the AP catalytic system, and the high-temperature decomposition peak of AP was reduced by 73.7 K. 15 The pyrolysis peak of AP was advanced by 95 K when the amount of the complex added was 10 wt %. 12 Cheng et al reported Pb-ANP y O/CNTs nanocomposites, which can reduce the pyrolysis peak of AP by nearly 100 K. 9 However, metallic elements have great limitations because of their high surface energy and tend to lead to agglomeration so that their catalytic activity is low, which has a great impact on the catalytic effect of AP thermal decomposition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent decades, catalysts applied in the field of catalytic AP have been extensively studied, such as metal oxides, metal particles, metal-based composites, and carbon nanomaterials. , In this article, Pb­(II) is chosen as the catalyst on the basis of the following considerations: lead metal has a good coordination ability and can easily chelate with multifunctional groups to form salts. The lead salt, as the active catalyst in the solid propulsion system, has a positive impact on the combustion rate and performance of the propellant. , Huo et al introduced a poly­(lead acrylate) (PAA-Pb) porous metal material into the AP catalytic system, and the high-temperature decomposition peak of AP was reduced by 73.7 K . The pyrolysis peak of AP was advanced by 95 K when the amount of the complex added was 10 wt % .…”
Section: Introductionmentioning
confidence: 99%